Transformasi Digital Pembelajaran Bahasa Inggris: Pelatihan Penerapan AI di SMA/SMK - Que, Stella Rose; Tanasale, Inggrit Olivin (Universitas Pattimura, 2024)
Digital transformation in education has encouraged the birth of various learning innovations, one of which is through the use of artificial intelligence (AI). This article aims to describe the implementation of training activities on the application of AI in learning English at the SMA/SMK level as part of the Community Service program. This activity was motivated by the need for teachers to develop learning methods that are more interactive, contextual, and in accordance with the demands of the digital era. The training focused on the utilization of AI-based platforms such as ChatGPT, Grammarly, and Quillbot that support the improvement of students' language skills, especially in the aspects of writing, reading, and speaking. The training method is designed in a participatory manner with a demonstrative approach and hands-on practice, so that participants can concretely understand the application of these technologies in learning. The results of the training evaluation showed a significant increase in teachers' understanding of the functions and benefits of AI in English classes, as well as the high enthusiasm of participants to integrate the technology into their lesson plans. This finding shows that AI training can be a strategic step in supporting the transformation of learning that is adaptive, innovative, and oriented towards improving 21st-century competencies. This activity also makes a positive contribution to strengthening the professional capacity of teachers in facing the challenges and opportunities of education in the digital era.